Natural killer cells in the lung: novel insight and future challenge in the airway diseases - Tommaso Pianigiani; Irene Paggi; Grace E. Cooper; Karl J. Staples; Melissa McDonnell; Laura Bergantini (ERJ Open Research)
Natural killer (NK) cells are innate lymphoid cells which are present in the lung as circulating and resident cells. They are key players both in airway surveillance and in crosstalk with (COPD) pathogenesis, and they seem to contribute to the development of bronchiectasis. In asthma, NK cell dysfunction was observed mainly in severe forms, and it can lead to a biased type-2 immune response and failure in the resolution of eosinophilic inflammation that characterise both allergic and eosinophilic phenotypes. Moreover, aberrant NK cell functions may interfere with antimicrobial immune response contributing to the frequency and severity of virus-induced exacerbations. In COPD, lung NK cells exhibit increased cytotoxicity against lung epithelium contributing to lung tissue destruction and emphysema. This cell destruction may be exacerbated by viral infections and cigarette smoke exposure through NKG2D-dependent detection of cellular stress. Lastly, in bronchiectasis, the airway NK cells might both promote neutrophil survival following stimulation by proinflammatory cytokines and promote neutrophil apoptosis. Systemic steroid treatment seemingly compromises NK activity, while biologic treatment with benralizumab could enhance NK cell proliferation, maturation and activation. This narrative review gives an overview of NK cells in airway diseases focusing on pathophysiological and clinical implications. Together, our findings emphasise the pleiotropic role of NK cells in airway diseases underscoring their possible implications as to therapeutical approaches.